Immunotherapies inducing immunogenic cell death in cancer: insight of the innate immune system - Calvillo-Rodríguez, Kenny Misael; Lorenzo-Anota, Helen Yarimet; Rodríguez-Padilla, Cristina; Martínez-Torres, Ana Carolina; Scott-Algara, Daniel (Frontiers in Immunology, 2023)
Cancer immunotherapies include monoclonal antibodies, cytokines, oncolytic viruses, cellular therapies, and other biological and synthetic immunomodulators. These are traditionally studied for their effect on the immune system's role in eliminating cancer cells. However, some of these therapies have the unique ability to directly induce cytotoxicity in cancer cells by inducing immunogenic cell death (ICD). Unlike general immune stimulation, ICD triggers specific therapyinduced cell death pathways, based on the release of damage-associated molecular patterns (DAMPs) from dying tumour cells. These activate innate pattern recognition receptors (PRRs) and subsequent adaptive immune responses, offering the promise of sustained anticancer drug efficacy and durable antitumour immune memory. Exploring how onco-immunotherapies can trigger ICD, either independently or in conjunction with immune activation, enhances our understanding of their mechanisms and potential for combination strategies. This review explores the complexities of these immunotherapeutic approaches that induce ICD, highlighting their implications for the innate immune system, addressing challenges in cancer treatment, and emphasising the pivotal role of ICD in contemporary cancer research.